2004
DOI: 10.1080/15017410409512654
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment, working life conditions, and gender

Abstract: The purpose of this article is to examine differences and similarities in working conditions and health status between men and women with hearing impairments. This article is based on a material collected with a comprehensive questionnaire, looking at psycho-social work environments and health status and answered by a total of 406 patients at two audiological clinics in Sweden. Examination of the data reveals a pattern of unfavourable conditions for hearing-impaired persons/employees when compared to a referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 9 publications
2
21
0
1
Order By: Relevance
“…Women with hearing difficulties are often found to be worse off than their male counterparts [28,31,34,54], which is in line with our results. Women seem to perceive their hearing impairment as being more negative than men do [59,60], possibly because the disability is generally associated with men [61] and affects skills traditionally associated with women, namely communication and nurturing roles [62].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Women with hearing difficulties are often found to be worse off than their male counterparts [28,31,34,54], which is in line with our results. Women seem to perceive their hearing impairment as being more negative than men do [59,60], possibly because the disability is generally associated with men [61] and affects skills traditionally associated with women, namely communication and nurturing roles [62].…”
Section: Discussionsupporting
confidence: 92%
“…Hearing difficulties has previously been associated with poorer health [14,31,54], work-related stress [14,30,31,54], and work-related accidents [26,55-57], which may eventually lead to sickness absence [30,33] and disability pension [25,33,34]. On the other hand, transitions from paid employment to unemployment, long-term sick leave, and even maternal leave have been associated with increased psychological distress [58], which may cause health problems, including hearing difficulties [24].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, performing a listening task in the presence of background noise has been shown to increase cognitive effort (perceived cost) in participants with normal hearing and hearing loss (Picou et al, 2017; Picou & Ricketts, 2014). Correspondingly, a growing body of literature suggests that sustained listening under a variety of adverse listening conditions (e.g., in noise, degraded stimuli, hearing impairment) can also lead to mental fatigue (e.g., Key et al, 2017; Alhanbali et al, 2017; Bess & Hornsby, 2014; Gellerstedt & Danermark, 2004; Hétu et al, 1988; Hornsby, 2013; Kramer et al, 2006). For instance, Antons et al (2012) found that 20 minutes of listening to degraded audio resulted in greater mental fatigue than listening to intact audio for the same duration.…”
Section: Introductionmentioning
confidence: 99%
“…Younger, actively employed hearing-impaired people in particular often suffer from poorer health than their coevals [9]. Many people with hearing loss have a hard time coping with the demands of modern working life.…”
Section: Hearing Impairments Affect Healthmentioning
confidence: 99%